Isaiah's Vision of Yahweh and Ethical Replication - Grey, Jacqueline (Old Testament essays, 2018)
This article explores Isaiah's vision of the thrice-holy Yahweh and his message of ethical replication. According to Elaine Scarry, the presence of beauty prompts replication. This will be adapted to consider the role of holiness as a driving factor in Isaiah's message of socialjustice. First, Isaiah is de-centred in his experience of Yahweh's beauty and terror. Secondly, Isaiah volunteered to embody the message of Yahweh and to call his community to similarly mirror Yahweh in their religious and moral life. By focusing on the use of Isaiah's key terminology of "the Holy One of Israel" in Isaiah 1-39, the expectation of ethical replication among the covenant community is examined. Thirdly, as this key term is also prevalent in chapters 40-66, arguably the expectation for ethical replication was continued by the disciples of Isaiah. This study reinforces holiness as having ethical as well as religious importance in Isaiah's message.